FORMULATION AND CHARACTERIZATION OF MUCOADHESIVE BUCCAL FILM OF RANITIDINE HYDROCHLORIDE USING STERCULIA FOETIDA GUM AS POLYMER - Dixit, G. R.; Chavhan, J. I.; P. UPADHYE, KANCHAN; MISRA, SUSHANT (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The aim of the present study was to develop buccal drug delivery system of Sterculia foetida gum and Ranitidine HCl. Buccal film of Ranitidine HCl was developed using mucoadhesive polymer S. foetida gums like. The prepared films were evaluated in terms of their physical characteristics and in vitro release. The formulation was optimized for the different concentration of S. foetida gum. The results of in vitro release studies showed that optimized formulation (A4) could sustain drug release (98.79%) for 12 hrs. The release profiles were subjected to various kinetic equations like Higuchi diffusion equation and Peppas exponential equation. The regression coefficient values of this kinetic equation are very nearer to one suggesting that plots are fairly linear and slope values of the Peppas equation is (>1) suggest that drug was released by diffusion mechanism following non-Fickian transport. Mucoadhesive buccal films of Ranitidine HCL sustained release, and non-Fickian transport of the drug from film was confirmed. Keywords: Ranitidine HCl, Buccal drug delivery system, Sterculia foetida gum, Sustaine release.